PENGARUH BERMAIN HIJAU HITAM TERHADAP KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 PEKANBARU - Novita, Mega; Zulkifli, Zulkifli; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine the effect of playing black green on children aged 5-6 years. This research was conducted at the Pmbina 3 Pekanbaru State Kindergarten in March 2018. This is pretest and posttest group design an experimental research with 30 children as samples. Type of instrument used in this study is the observation using a sheet to record about activities that occurred during a given treatment. Based on the hypothesis test results obtained are the shaping technique is influence on Emotional intelligence children ages 5-6 years in TK Negeri Pembina 3 pekanbaru. Retrieved t count at 8,613 with sig 0000, because sig <0.05 then we can conclude that there are influence on the Emotional intelligence is significant between class with playing green black and without playing green black. Hypothesis testing can be seen at tcount= 8,613> t table = 2,048 it has been suggested that there is a significant influence in results between the control class and experiment class. The playing green black had a significant effect towards children’s age 5-6 years old Emotional intelligence, at 63,69%. This is known from the different results Emotional intelligence on control class and expriment class with given playing green black treatment.Key Words: Emotional intelligence, playing green black